Diabetes in der Schwangerschaft praxisorientiertes Wissen zu Gestationsdiabetes, Diabetes mellitus Typ 1 und 2, MODY - Stupin, Jens; Schäfer-Graf, Ute 1959-; Hummel, Michael (De Gruyter, 2020)
How does a practitioner cope with the increasing prevalence of diabetes in pregnancy? Written by diabetologists, obstetricians, and neonatologists, this book explains theoretical principles as well as practical therapeutic strategies and standards along with case examples. It develops a practical guideline for obstetricians, neonatologists, midwives, diabetologists, and diabetes counselors
Description based on online resource; title from PDF title page (publisher's Web site, viewed 06. Apr 2020)
Keywords: Diabetes; Gestationsdiabetes; Glukosemessung; MODY; Schwangerschaft; Typ-1 Diabetes; Typ-2 Diabetes; gestational diabetes; glucose measurement; pregnancy; type-1 diabetes; type-2 diabetes; MEDICAL / Clinical Medicine; Diabetes mellitus; Schwangerschaftsdiabetes